Esfingolípidos y cáncer de vejiga: identificando potenciales blancos terapéuticos en su metabolismo y señalización - Mercado C., Alejandro; Gallegos M., Iván; Marchant G., Fernando; Reyes O., Diego; Castellón V., Enrique (Revista Hospital Clínico Universidad de Chile, 2013)
Bladder cancer is mostly diagnosed at non-muscle invasive stages. Despite treatment, more than 50% of the cases recur and 10-15% progress to muscle-invasive stages. Available therapies to reduce recurrence and progression are suboptimal. Identification of new potential therapeutic targets is needed. Lipids are not only structural molecules of the membranes. There are numerous examples of lipids mediating actions within the cells. Specifically, sphingolipids like ceramide, sphingosine and sphingosine-1-phosphate (S1P) have been described to be involved in the control of cell growth, proliferation and migration, all of which has been linked to cancer. The pro-apoptotic effects of ceramide and sphingosine are opposed by S1P. Therefore, the fate of the cell can be modulated by changing the ratio of these sphingolipids (the rheostat model). S1P promotes cell proliferation, growth, survival, migration, invasion and resistance to drugs and radiation, in part mediated by S1P membrane receptors (S1PR1-5). Over expression of S1P producing enzymes and increased S1P levels has been described in many cancers. No descriptions have been done in human samples of bladder cancer. However, few reports using bladder cancer cell lines suggest that the metabolic and signaling pathway of S1P can be a potential target for the treatment of bladder cancer.